2012
DOI: 10.1039/c2ob26793d
|View full text |Cite
|
Sign up to set email alerts
|

A furan Diels–Alder cycloaddition approach to scyphostatin analogues

Abstract: The synthesis of two diastereoisomers of the epoxycyclohexenone core of scyphostatin, a naturally occurring sphingomyelinase inhibitor, has been achieved via a common oxabicyclic intermediate. The diastereomeric intermediates are accessed by stereodivergent oxidative functionalisation processes, followed by a Lewis acid mediated ring opening rearrangement reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Comparison of 1 H NMR shifts and coupling constants with those of similar known trihydroxyalkylcyclohexenones was not definitive in determining the relative configuration. 7,8,10 However, the observed coupling constants of H-2 and H-3 in its 1 H NMR spectrum (H-2, dd, J = 1.1, 10.2 Hz; H-3, ddd, J = 1.1, 3.7, 10.2 Hz) are consistent with those of similar alkylcyclohexenones with the same relative configuration as proposed. 14 In order to further support our proposed relative configuration, the cyclic double bond of 2 was selectively reduced with diphenylsilane in the presence of ZnCl 2 and Pd(PPh 3 ) 4 to give the substituted cyclohexanone 4 .…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Comparison of 1 H NMR shifts and coupling constants with those of similar known trihydroxyalkylcyclohexenones was not definitive in determining the relative configuration. 7,8,10 However, the observed coupling constants of H-2 and H-3 in its 1 H NMR spectrum (H-2, dd, J = 1.1, 10.2 Hz; H-3, ddd, J = 1.1, 3.7, 10.2 Hz) are consistent with those of similar alkylcyclohexenones with the same relative configuration as proposed. 14 In order to further support our proposed relative configuration, the cyclic double bond of 2 was selectively reduced with diphenylsilane in the presence of ZnCl 2 and Pd(PPh 3 ) 4 to give the substituted cyclohexanone 4 .…”
supporting
confidence: 82%
“…This was consistent with the 13 C NMR data, which showed 10 signals at approximately δ 29 as well as signals at δ 23.0 (C-2′), 22.7 (C-18′), and 14.7 (C-19′). The NMR spectroscopic data are comparable to those of other known trihydroxyalkylcyclohexenone derviatives. The presence of a double bond within the alkyl chain was indicated by a signal at δ 5.34 (2H, m) in the 1 H NMR spectrum as well as by COSY correlations from δ 5.34 (H-10′, H-11′) to δ 2.00 (H-9′, H-12′).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Owing to its impressive bioactivity and a novel bipolar lipid-like construct, scyphostatin ( 1 ) has evoked sustained interest from both synthetic and medicinal chemistry communities. Several total syntheses and model studies, targeting its polar cyclohexenoid core and structural analogues, have been reported during the past decade. In the context of evaluating the therapeutic space around the natural product for SAR studies and diversity generation, it was further recognized that it is mainly the long hydrophobic chain in 1 (green box), readily installed through N -acylation of the side arm on the hydrophilic segment, that offers considerable latitude.…”
mentioning
confidence: 99%
“…To date, a number of naturally occurring inhibitors of SMase have been described [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Several synthetic inhibitors, such as a carbamate analog, carbon-analog or fluorinated carbon-analog, that mimic the phosphate ester moiety of phosphocholine by substituting it with stable functional groups have also been developed [29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%